2011
DOI: 10.1002/asia.201100024
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed Sequential CC and CN Bond Formations for the Synthesis of N‐Heterocycles: Exploiting Protecting Group‐Directed CH Activation under Modified Reaction Conditions

Abstract: Easy & efficient: A Pd‐catalyzed domino olefination/conjugate addition reaction of N‐Ts‐2‐arylanilines with activated olefins has been achieved at ambient temperature under the newly defined reaction conditions. This process highlighted the directing effect of the N‐protecting group in CH activation, displayed broad substrate scope with wide functional group compatibility; thus rendering a straightforward entry to a wide variety of N‐heterocycles such as dihydrophenanthridines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…This re -1 1 2 2 3 3 4 4 5 5 6 6 7 7 8 8 9 9 10 10 11 11 12 12 13 13 14 14 15 15 16 16 17 17 18 18 19 19 20 20 21 21 22 22 23 23 24 24 25 25 26 26 27 27 28 28 29 29 30 30 31 31 32 32 33 33 34 34 35 35 36 36 37 37 38 38 39 39 40 40 41 41 42 42 43 43 44 44 45 45 46 46 47 47 48 48 49 49 50 50 51 51 52 52 53 53 54 54 55 55 56 56 57 57 action provided a new route for the preparation of tricyclic nitrogen-containing heterocycles and brought a lot of attention to this field. [4] They used K 2 S 2 O 8 as an inexpensive, easy-tohandle oxidant in the tosylamide-directed transformation. [4] They used K 2 S 2 O 8 as an inexpensive, easy-tohandle oxidant in the tosylamide-directed transformation.…”
Section: Annulation Of Amides With Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…This re -1 1 2 2 3 3 4 4 5 5 6 6 7 7 8 8 9 9 10 10 11 11 12 12 13 13 14 14 15 15 16 16 17 17 18 18 19 19 20 20 21 21 22 22 23 23 24 24 25 25 26 26 27 27 28 28 29 29 30 30 31 31 32 32 33 33 34 34 35 35 36 36 37 37 38 38 39 39 40 40 41 41 42 42 43 43 44 44 45 45 46 46 47 47 48 48 49 49 50 50 51 51 52 52 53 53 54 54 55 55 56 56 57 57 action provided a new route for the preparation of tricyclic nitrogen-containing heterocycles and brought a lot of attention to this field. [4] They used K 2 S 2 O 8 as an inexpensive, easy-tohandle oxidant in the tosylamide-directed transformation. [4] They used K 2 S 2 O 8 as an inexpensive, easy-tohandle oxidant in the tosylamide-directed transformation.…”
Section: Annulation Of Amides With Alkenesmentioning
confidence: 99%
“…On the basis of this seminal study, modified reaction conditions were recently reported by Youn and co-workers (Scheme 3). [4] They used K 2 S 2 O 8 as an inexpensive, easy-tohandle oxidant in the tosylamide-directed transformation. Compared to the earlier report, this reaction proceeded at ambient temperature by using a p-TsOH additive along with a trifluoroacetic acid/dichloromethane co-solvent.…”
Section: Annulation Of Amides With Alkenesmentioning
confidence: 99%
“…In this case, dehydrogenative N-C bond forming cyclization of the cycloadducts (16a,b) yields straightforwardly natural product-like pyrrolocarbazoles (17a,b). Thus, isoindoline-1,3-dione (16a) was subjected to a palladium catalysed dehydrogenative cyclization, using phenyliodine (III) diacetate (PIDA) as an external oxidant [22][23][24][25]. The reaction is completed under microwave irradiation at 110 °C in hexafluoroisopropanol (HFIP) in just one minute, affording pyrrolocarbazole 17a in 58% yield (Scheme 5) [19].…”
Section: Resultsmentioning
confidence: 99%
“…According to this pathway, the coordination of the alkene prior to the β-C elimination precludes the release of the C4-arylation product. (18) 2-Thienyl-N-tosylaniline undergoes regioselective DHR with ethyl acrylate leading to the C3 substituted thiophene and a fused heterocycle due, according to Youn and co-workers, to subsequent cyclization of the C3 substituted thiophene (Equation (19)) [55]. We will come back in Sub-chapter 4.1. to the mechanism and catalytic cycle of substrates with a directing group ( Scheme 9).…”
Section: Scheme 3 Plausible Pathways Of Vicinal Difunctionalizationsmentioning
confidence: 99%